FRAMING THE PAST, SHAPING THE PRESENT: HISTORICAL TV SERIES IN TURKIYE AND SOUTH KOREA1 - Gurel, Seda; Okur, Mehmet Akif (Kafkas University IIBF, 2025)
The capacity of creative content to construct civil societies' consent leads historical TV series, as narratives that reflect political stances, to be questioned. Since the Cold War, T & uuml;rkiye and South Korea have been influenced by US-centered Western main flow but have also produced alternative flows since the 2000s.This study classifies historical fictions by platforms-national channels and the American digital platform Netflix-and comparatively analyzes selected fictions using the Narrative Policy Framework (NPF). The aim is to reveal the relationship between the narratives' prominent characters and their political reflections through governments' global agendas. The study concludes that narratives selected from state cultural institutions tend to be more nationalist, while narratives from Netflix, despite local production, reflect the influence of the hegemonic cultural center. This research contributes to literature by applying the NPF as a unique method, comparing Turkish and South Korean cultural elites' narratives, and interpreting political reflections of prominent characters.
Keywords: hegemonic system; Turkish cultural industry; South Korean cultural & imath; ndustry; American; cultural industry; POWER; TELEVISION; MARKET; IMPACT; FLOW; Business & Economics